2005
DOI: 10.1297/cpe.14.17
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Heterozygous K83E and R257X Mutations of the AIRE-1 Gene in 46 Children with Type 1 Diabetes and 44 Children with Graves' Disease

Abstract: Type 1 diabetes mellitus (DM) and Graves’ disease are autoimmune diseases, and a number of genetic factors, including HLA and CTLA-4 genes, have been reported to contribute to their etiology. The gene responsible for autoimmune polyendocrinopathy- candidiasis-ectodermal dystrophy (APECED) has been cloned and named the autoimmune regulator-1 (AIRE-1) gene. AIRE-1 protein is thought to be a transcription regulatory protein and to have a role in the maintenance of immunological tolerance. The aim of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…( 12 ) and Shimura et al . ( 13 ) reported that there were high correlations between the bone age evaluated by BonAge® and the GP or TW2 methods. In contrast, Khan et al .…”
Section: Bone Age Assessment Methodsmentioning
confidence: 99%
“…( 12 ) and Shimura et al . ( 13 ) reported that there were high correlations between the bone age evaluated by BonAge® and the GP or TW2 methods. In contrast, Khan et al .…”
Section: Bone Age Assessment Methodsmentioning
confidence: 99%
“…They showed that a good correlation existed with SBA results and TW2 method. [ 50 ] In contrast, Khan et al . suggested that ultrasonic assessment should not yet be considered a valid replacement for radiographic BA determination.…”
Section: B Ackground Of S Keletal mentioning
confidence: 99%
“…The limitations of ultrasound assessment include its operator dependence, the likely lower intrarater and interrater reliability of assessment, and the difficulties with standardization of documentation and imaging transfer. Although, initial studies on a comparison with the GP atlas standards show promising results,[ 41 51 ] this method needs to be evaluated in a multiethnic population with a large sample size before its wide-scale use. [ 52 53 54 55 ]…”
Section: B Ackground Of S Keletal mentioning
confidence: 99%
“…A result of one of these trials is BonAge ® (Sunlight Medical Ltd, Tel Aviv, Israel) which consists of a device that performs an ultrasonographic examination and software that calculates the BA on the basis of this examination ( 19 , 40 , 41 , 42 , 43 ). BonAge ® measures the ossifying cartilage structures of the wrist as an ultrasonic wave passes through the subject’s distal radius and ulnar epiphysis.…”
Section: Introductionmentioning
confidence: 99%